Short-Term Outcomes of Pediatric Renal Transplantation in Nigeria; A Single-Center Experience: Pediatric renal transplantation in Nigeria - Anigilaje, Emmanuel Ademola; Olatise , Olalekan; Kextero, Maduadi; Martins , Igbokwe (Journal of Pediatric Nephrology, 2021)
Background and Aim: Renal transplantation (RT) is the preferred treatment modality for children with end-stage kidney disease (ESKD). Unfortunately, RT remains inaccessible for children with ESKD in resource-constrained countries. This case-series describes a short-term follow-up of RT in three children in the Zenith Medical and Kidney Centre (ZMKC), Abuja, Nigeria. Methods: The immediate allograft function (IAF), allograft functions and recipients’ survival at 6-24 months of follow-up of three pediatric ESKD patients from January 2018 to January 2020 were described. Allograft functions were assessed using serum creatinine and Doppler ultrasound scan. RT involved the use of basiliximab and thymoglobulin for induction therapy and oral prednisolone, tacrolimus and mycophenolate mofetil for maintenance immunosuppressive therapy. Results: Recipients including two males and one female were 9-17 years (mean age: 12 years). Primary steroid-resistant focal segmental glomerulosclerosis nephrotic syndrome, congenital posterior urethral stricture and lupus nephritis were the causes of ESKD in recipients seen over 24 months, 6 months, and 6 months, respectively. The female recipient had lupus nephritis. The IAF was excellent in all the cases. All the three children are alive with good allograft functions at the end of their respective follow-up period. Conclusion: This case-series showed that a successful pediatric RT program is feasible in a resource-constrained setting like Nigeria.